2016
DOI: 10.1038/onc.2016.427
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-like transcriptional reprogramming mediates metastatic resistance to mTOR inhibition

Abstract: Inhibitors of the mechanistic target of rapamycin (mTOR) are currently used to treat advanced metastatic breast cancer. However, whether an aggressive phenotype is sustained through adaptation or resistance to mTOR inhibition remains unknown. Here, complementary studies in human tumors, cancer models and cell lines reveal transcriptional reprogramming that supports metastasis in response to mTOR inhibition. This cancer feature is driven by EVI1 and SOX9. EVI1 functionally cooperates with and positively regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 61 publications
7
28
0
Order By: Relevance
“…A high level of expression of EVI1 in this subtype-but not in the other KIRC subtypes (CC-e.1-2) and complete cohort-was found to be significantly associated with poorer outcome, as measured by a multivariate (including age, gender, and tumor stage) Cox regression analysis of progression-free interval (PFI; Figure 2B). The CC-e.3 subtype was identified by TCGA as the subgroup with a higher relative level of expression of markers of the epithelial-mesenchymal transition [30], which is consistent with the functional associations of EVI1 described in some cancer settings [6,7,15]. Indeed, EVI1 expression in CC-e.3 tumors was found to be positively co-expressed with several metastasis-, invasion-and integrin-related curated gene sets ( Supplementary Table S2).…”
Section: Evi1 Overexpression Confers Ccrcc Cell Resistance To Everolimussupporting
confidence: 77%
See 3 more Smart Citations
“…A high level of expression of EVI1 in this subtype-but not in the other KIRC subtypes (CC-e.1-2) and complete cohort-was found to be significantly associated with poorer outcome, as measured by a multivariate (including age, gender, and tumor stage) Cox regression analysis of progression-free interval (PFI; Figure 2B). The CC-e.3 subtype was identified by TCGA as the subgroup with a higher relative level of expression of markers of the epithelial-mesenchymal transition [30], which is consistent with the functional associations of EVI1 described in some cancer settings [6,7,15]. Indeed, EVI1 expression in CC-e.3 tumors was found to be positively co-expressed with several metastasis-, invasion-and integrin-related curated gene sets ( Supplementary Table S2).…”
Section: Evi1 Overexpression Confers Ccrcc Cell Resistance To Everolimussupporting
confidence: 77%
“…In addition to myeloid leukemia, overexpression of EVI1 has been associated with aggressive phenotypes of breast cancer, colorectal, lung, ovarian, pancreatic, and prostate cancer [5][6][7][8][9][10][11][12][13].…”
Section: Evi1 Overexpression Is Associated With Progression Features mentioning
confidence: 99%
See 2 more Smart Citations
“…CSCs can self‐renew and differentiate to different types of mature cancer cells, leading to the development and progression of malignant tumours . BCSCs are major players of drug resistance and can promote the development of TAM resistance in breast cancer by increasing their stemness . In this study, we found that DLG5 silencing increased the frequency of CD44 + /CD24 − and ALDH + BCSCs, the formation of mammospheres, anchorage‐independent growing clonogenicity and Oct4 and c‐MYC expression in ER + MCF7 cells while induction of DLG5 overexpression decreased them in TAM‐resistant LCC2 cells.…”
Section: Discussionmentioning
confidence: 53%